Evaluation of the effect of flocculation on harvesting of microalgaenannochloropsis SP (2018)
Microalgae have recently emerged as an attractive source of products for the food, energy and pharmaceutical industries due to their high biomass productivity, metabolic versatility and environmental sustainability. This work focuses on the effect of flocculation on the harvesting of microalgae Nannochloropsissp. Through a three-factor experimental design. The most suitable conditions for flocculation were determined based on flocculant (AlCl3) dosage, pH and culture time. In addition, flocculant adding-pH adjustment methods were studied and harvesting was performed according to the method that provided the best results. The pH adjustment after flocculant addition showed higher flocculation efficiency (above 90%) compared to the reverse process. It was also found that the microalgae cells exhibited spontaneous sedimentation, suggesting that the use of flocculant is not required for biomass collection.